Pengaruh Penggunaan Media Gambar Dalam Buku Bahasa Arab Mts Terhadap Pemahaman Maharah Qirā’ah Siswa Kelas IX MTsN 1 Bandar Lampung - Aulia Aulia; Yeni Lailatul Wahidah; Intan Muflihah; Guntur Cahaya Kesuma (Ukazh : Journal of Arabic Studies, 2026)
This research is motivated by the low understanding of students' maharah qirā'ah in Arabic language learning due to the less than optimal use of visual learning media. This study aims to determine the effect of the use of image media in Arabic language books on the understanding of maharah qirā'ah of grade IX students of MTsN 1 Bandar Lampung. The research method uses a quantitative approach with a quasi-experimental design of the pretest-posttest control group design type. The research sample consists of class IX B as the experimental class and IX C as the control class. Data collection techniques use tests, observations, and documentation. Data analysis is carried out through normality tests, homogeneity, Independent Samples T-Test, and N-Gain tests using IBM SPSS 25. The results of the study show a significance value (Sig. 2-tailed) of 0.001 <0.05 which means there is a significant difference between the experimental class and the control class. The average posttest score of the experimental class is 82.58, higher than the control class of 70.13. Furthermore, the N-Gain test results showed that the experimental class obtained a score of 0.69, categorized as quite effective, while the control class obtained a score of 0.42, categorized as less effective. Thus, the use of visual media in Arabic textbooks significantly increased students' understanding of maharah qirā'ah.